1979
DOI: 10.1136/thx.34.3.324
|View full text |Cite
|
Sign up to set email alerts
|

Demeclocycline in the treatment of the syndrome of inappropriate secretion of antidiuretic hormone.

Abstract: Fourteen patients with the syndrome of inappropriate secretion of antidiuretic hormone (SIADH) have been treated with demethylchlortetracycline (demeclocycline) 1200 mg daily. In 12 patients the underlying lesion was malignant. The serum sodium returned to normal (> 135 mmol/l) in all patients after a mean of 8-6 days (SD+5-3 days). Blood urea rose significantly from the pretreatment level of 4-2±2-3 mmol/l to 10-1±5-1 mmol/l at ten days (p<0 001). The average maximum blood urea was 13-4-6-8 mmol/l. In four pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…We also found several observational reports of acute kidney injury with demeclocycline (214,215,218,219,222,223,224,225,226,227,228,229,230,231,232); a single case report of confusion and somnolence with lithium (220) and unspecified neurological abnormalities with phenytoin (233). Finally, we identified two reports of adverse events with fluid restriction.…”
Section: Rationale † Why This Question?mentioning
confidence: 63%
See 1 more Smart Citation
“…We also found several observational reports of acute kidney injury with demeclocycline (214,215,218,219,222,223,224,225,226,227,228,229,230,231,232); a single case report of confusion and somnolence with lithium (220) and unspecified neurological abnormalities with phenytoin (233). Finally, we identified two reports of adverse events with fluid restriction.…”
Section: Rationale † Why This Question?mentioning
confidence: 63%
“…We found several case series demonstrating an increase in serum sodium concentration after 2-7 days for urea (202,203,204,205,206), demeclocycline (207), loop diuretics in combination with oral NaCl (123,125,208), phenytoin (209) and fluid restriction (210). We also identified case series of patients experiencing an increase in serum sodium over a longer time period of up to 12 months for urea (211,212,213), up to 3 weeks for demeclocycline (214,215,216,217,218,219), up to 20 weeks for lithium (220), up to 150 days for furosemide with oral NaCl (221) and up to 30 days in phenytoin (220).…”
Section: Rationale † Why This Question?mentioning
confidence: 88%
“…All four studies reported an increase in mean serum sodium levels during treatment with demeclocycline at doses of up to 1200 mg/day 20, 22, 26, 27.…”
Section: Resultsmentioning
confidence: 98%
“…In total, 16 non‐RCTs were considered relevant, comprising six cohort studies (four observational studies 20, 22, 26, 27, two retrospective chart analyses 21, 28, and 10 case reports 29, 30, 31, 32, 33, 34, 35, 36, 37, 38 (Tables 2 and 3, respectively); no cost‐effectiveness or HRQoL studies were identified. Quality assessments for all studies other than case reports are presented (Appendix C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation